A STUDY OF THE DECAYS OF TAU LEPTONS PRODUCED ON THE Z-RESONANCE AT LEP - Abreu, P; Adam, W; Adye, T; Agasi, E; Alekseev, G; Allen, P; Almehed, S; Alvsvaag, S; Amaldi, U; Anassontzis, E; Andreazza, A; Antilogus, P; et al. (1992)
From the analysis of a data sample corresponding to an integrated luminosity of 4.63 pb-1 taken during the 1990 run of LEP at centre of mass energies between 88.2 GeV an 94.2 GeV, the tau decays Mathematical expression and their charge conjugates have been studied. The following branching ratios have been measured; Mathematical expression, Mathematical expression, Br(τ- → π- (K-)vτ)=11.9±0.7±0.7%, BR (τ- → ρ- vτ)= 22.4±0.8±1.3%, in good agreement with world averages. The measured electronic and muonic branching ratios lead to a measurement of the strong coupling constant, αs (mτ) = 0.26-0.12+0.09. Extrapolating the αs value from mτ to mZ yields αs (mZ) = 0.109-0.028+0.012. The average polarization Pτ of taus produced in Z → τs τs decays has also been measured using the above decay modes. The weighted mean of the polarizations obtained from the four decay modes is Pτ=-0.24±0.07. This value of Pτ gives, in the improved Born approximation, a ratio between the axial and vector coupling constants of the tau of υτ/aτ = 0.12 ± 0.04, and hence a value of the effective electroweak mixing parameter sin2 θW(mZ2). © 1992 Springer-Verlag.